Pandemocracy in Europe Power, Parliaments and People in Times of Covid-19 - Kettemann, Matthias C (Bloomsbury Academic, 2021)
This edited collection looks at the dramatic impact of COVID-19 and the fight against the virus on Europe's democracies, with case studies of the UK, Germany, Italy, Sweden, Hungary, Switzerland, France and Estonia.